The impact of socio-cultural factors on entrepreneurial failure in Soran city - Salih, Ehsan; Mahmood, Emdad Khaleel; Mustafa, Zhian Bwrhan; Ado, Samian Karim; Ahmad, Rebar Maghdid (Review of Islamic Social Finance and Entrepreneurship, 2024)
Purpose – The purpose of this study is to explore the impact of socio-cultural factors on entrepreneurial failure in Soran City, aiming to identify the key cultural influences that affect entrepreneurial outcomes and to propose a theoretical framework that explains these dynamics.Methodology – The research employed a qualitative approach, conducting structured interviews with 10 purposively sampled entrepreneurs who hold leadership roles in the entrepreneurial community of Soran. Data collection involved preparing, structuring, and organizing interview transcripts, followed by coding to identify themes and patterns. The analysis then focused on interpreting the socio-cultural significance of the identified factors in relation to entrepreneurial failure.Findings – This study found that socio-cultural factors significantly influence entrepreneurial outcomes. The key factors identified included societal values and norms, gender roles, family background, and educational background. While gender did not emerge as a prominent factor in this study, other socio-cultural elements played a critical role in shaping entrepreneurial success or failure.Implications – The findings highlight the importance of understanding cultural nuances in entrepreneurship. The study suggests that promoting an entrepreneurial culture through targeted community training workshops, educational courses, and media initiatives could enhance entrepreneurial activity and reduce the risk of failure in Soran.Originality – This research introduces the multidimensional socio-cultural constraints theory (MDSC Theory), which provides a novel explanation of how various socio-cultural factors cumulatively contribute to entrepreneurial failure. This theory offers a new perspective on the challenges faced by entrepreneurs in culturally specific contexts, emphasizing the need for culturally informed strategies to foster entrepreneurial success.